Pathophysiological Roles of Amyloidogenic Carboxy-Terminal Fragments of the β-Amyloid Precursor Protein in Alzheimer's Disease - Keun-A Chang; Yoo-Hun Suh (Elsevier, 2005)
Several lines of evidence suggest that some of the neurotoxicity in Alzheimer's disease (AD) is attributed to proteolytic fragments of amyloid precursor protein (APP) and β-amyloid (Aβ) may not be the sole active component involved in the pathogenesis of AD. The potential effects of other cleavage products of APP need to be explored. The CTFs, carboxyterminal fragments of APP, have been found in AD patients' brain and reported to exhibit much higher neurotoxicity in a variety of preparations than Aβ. Furthermore CTFs are known to impair calcium homeostasis and learning and memory through blocking LTP, triggering a strong inflammatory reaction through MAPKs- and NF-κB-dependent astrocytosis and iNOS induction. Recently, it was reported that CTF translocated into the nucleus, binding with Fe65 and CP2, and in turn, affected transcription of genes including glycogen synthase kinase-3β, which results in the induction of tau-rich neurofibrillary tangles and subsequently cell death. Spatial memory of transgenic (Tg) mice overexpressing CT100 was significantly impaired and CTFs were detected in the neurons as well as in plaques of the Tg mice and double Tg mice carrying CT100 and mutant tau. In this review, we summarize observations indicating that both CTF and Aβ may participate in the neuronal degeneration in the progress of AD by differential mechanisms. Keywords:: Alzheimer's disease, amyloid precursor protein (APP), carboxy-terminal fragment of APP, β-amyloid